2021
DOI: 10.1111/ele.13946
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient identity modifies the destabilising effects of eutrophication in grasslands

Abstract: Nutrient enrichment can simultaneously increase and destabilise plant biomass production, with co‐limitation by multiple nutrients potentially intensifying these effects. Here, we test how factorial additions of nitrogen (N), phosphorus (P) and potassium with essential nutrients (K+) affect the stability (mean/standard deviation) of aboveground biomass in 34 grasslands over 7 years. Destabilisation with fertilisation was prevalent but was driven by single nutrients, not synergistic nutrient interactions. On av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 79 publications
6
28
1
Order By: Relevance
“…Addition of NPK +µ reduced the relative distribution of C and N in MAOM versus POM (fMAOM-C and -N) as compared to the control and P, respectively. These findings align with previous NutNet work that suggests grassland biomass production is co-limited by N, P, and K, as adding these together increases aboveground plant growth (Fay et al 2015;Carroll et al 2021), as we also found in our sites (Supplementary Fig. 3).…”
Section: Biogeochemistry 1supporting
confidence: 93%
“…Addition of NPK +µ reduced the relative distribution of C and N in MAOM versus POM (fMAOM-C and -N) as compared to the control and P, respectively. These findings align with previous NutNet work that suggests grassland biomass production is co-limited by N, P, and K, as adding these together increases aboveground plant growth (Fay et al 2015;Carroll et al 2021), as we also found in our sites (Supplementary Fig. 3).…”
Section: Biogeochemistry 1supporting
confidence: 93%
“…Plant communities on infertile soils often exhibit resource‐conservative functional traits, which may limit their responses to climate change (Fernandez‐Going et al, 2012). Conversely, they may also be more vulnerable to climate variation once nutrient limitations are relieved under eutrophication (Carroll et al, 2022). At present, the response of the stability of plant communities to various global changes along a soil fertility gradient and the underlying mechanisms remain unelucidated.…”
Section: Introductionmentioning
confidence: 99%
“…climate, soil properties, treatment intensity and duration) affect the responses of grassland stability? To address these questions, we test three interrelated hypotheses: (1) nutrient addition would decrease the temporal stability of grasslands by lessening nutrient limitations (Bai et al, 2010; Carroll et al, 2022); (2) both plant species richness (Hautier et al, 2015) and dominant plant functional group (Mackie et al, 2019; Shi et al, 2016) would play an important role in regulating stability responses to global changes and (3) community stability would be less affected by global changes in grasslands with lower soil fertility (Fernandez‐Going et al, 2012), higher climate variability (Ciemer et al, 2019), with low intensity treatments and with treatments that occurred only over short durations.…”
Section: Introductionmentioning
confidence: 99%
“…4). Consistent with previous analyses, we found that nutrient addition may decrease invariability through decreasing species richness (Hautier et al ., 2015; Carroll et al ., 2021), but this indirect negative effect, together with the negative effects through resilience were offset by the positive effects through resistance. Combined, nutrient addition did not impact invariability.…”
Section: Discussionmentioning
confidence: 99%
“…In grasslands, nutrient addition has been shown to decrease resistance in aboveground primary productivity during dry climate extremes as well as temporal invariability, while its effects on resilience after dry climate extremes are mixed (Tilman & Downing, 1994; Xu et al ., 2014; Hautier et al ., 2015; Bharath et al ., 2020; Meng et al ., 2021; Van Sundert et al ., 2021; Carroll et al ., 2021). However, to date, few empirical studies have investigated the impact of nutrient addition on resistance during and resilience after wet climate extremes, which are becoming increasingly frequent just as dry climate extremes globally (IPCC, 2019).…”
Section: Introductionmentioning
confidence: 99%